2007
DOI: 10.1002/bjs.5721
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgeon volume and specialization on short-term outcomes in colorectal cancer surgery

Abstract: High-volume surgeons had lower perioperative mortality rates for elective surgery, and were more likely to use restorative rectal procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 13 publications
5
94
2
1
Order By: Relevance
“…Previous research has reported improved outcomes among patients with rectal cancer who are treated by surgeons with subspecialty training, including increased use of sphincter-preserving surgery, [12][13][14][15] decreased local recurrence, 12,16 decreased anastomotic leak, 16,17 decreased postoperative mortality 16 and improved disease-specific survival. 16,18 It has been suggested that this variation in outcomes may reflect differences in surgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported improved outcomes among patients with rectal cancer who are treated by surgeons with subspecialty training, including increased use of sphincter-preserving surgery, [12][13][14][15] decreased local recurrence, 12,16 decreased anastomotic leak, 16,17 decreased postoperative mortality 16 and improved disease-specific survival. 16,18 It has been suggested that this variation in outcomes may reflect differences in surgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth period covered the years 2010 to 2013. 1757 patients identified from previous study [26] 67 with missing data 34 with data found Based on the between-hospital differences in average annual pouch procedures performed, we categorized hospital volume as very low (1-5 cases/year), low (6-10 cases/year), intermediate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) cases/year) and high (> 20 cases/year). For this categorization, we divided the total number of procedures performed at a department by the total number of calendar years in which pouch procedures were performed.…”
Section: Covariatesmentioning
confidence: 99%
“…While specialization of surgery has been found to improve perioperative outcomes for a wide variety of procedures, especially in the treatment of malignant conditions [19,20], the benefits of specialization in primary pouch surgery are less documented, since most studies examining risk factors for pouch failure are single-centre cohort studies [7]. Of the existing multicentre, national cohort studies on pouch failure, two are limited by short follow-up (median 4.8 and 5.4 years, respectively) [21,22] while a third used a nonvalidated administrative claims code of abdominoperineal excision to define pouch failure [23].…”
Section: Introductionmentioning
confidence: 99%
“…This finding was confirmed in a recent study from Hawkins et al Surgical trainees operating unsupervised by consultants had more surgery specific postoperative complications [16,17]. Borowski et al did not find a reduced risk of perioperative death in emergency colorectal cancer surgery for high-volume surgeons [18]. For long term survival after colorectal cancer surgery, a high surgeon's annual caseload was found to be an independent beneficial prognostic factor [19].…”
Section: Discussionmentioning
confidence: 80%